Proceedings of the 38th International Conference on Software Engineering 2016
DOI: 10.1145/2884781.2884826
|View full text |Cite
|
Sign up to set email alerts
|

Work practices and challenges in pull-based development

Abstract: The pull-based development model is an emerging way of contributing to distributed software projects that is gaining enormous popularity within the open source software (OSS) world. Previous work has examined this model by focusing on projects and their owners-we complement it by examining the work practices of project contributors and the challenges they face.We conducted a survey with 645 top contributors to active OSS projects using the pull-based model on GitHub, the prevalent social coding site. We also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(73 citation statements)
references
References 51 publications
2
56
0
Order By: Relevance
“…Since we do not accurately know the number of software developers in the world, nor how to reach them, finding a sample that would generalize to the population of software developers is a challenge. We used the GitHub social coding community as an avenue for reaching software developers that would represent the population of developers well enough, following several previous studies (e.g., Gousios et al (2016)). GitHub has more than 30 million visitors each month (Doll, 2015) and is, as far as we can tell, the largest social coding community in the world.…”
Section: Sampling Strategymentioning
confidence: 99%
“…Since we do not accurately know the number of software developers in the world, nor how to reach them, finding a sample that would generalize to the population of software developers is a challenge. We used the GitHub social coding community as an avenue for reaching software developers that would represent the population of developers well enough, following several previous studies (e.g., Gousios et al (2016)). GitHub has more than 30 million visitors each month (Doll, 2015) and is, as far as we can tell, the largest social coding community in the world.…”
Section: Sampling Strategymentioning
confidence: 99%
“…As such projects are relatively decentralized communities, our research is also in conversation with scholarship on other OSS projects that follow this model, as well as communities like Wikipedia. Our study found various issues around topics extensively discussed in these literatures, including incentives and motivations (Balestra et al 2017), onboarding newcomers (Steinmacher et al 2015), social interactions on collaborative platforms (de Souza et al 2016), work distribution and decentralized management (Gousios et al 2016), and the overall project health and success (Crownton et al 2003;Bangerth and Heister 2013). Such research has extensively discussed tensions between centralization and decentralization in peer production communities.…”
Section: Peer Production Communitiesmentioning
confidence: 72%
“…The source code runs through a compiler to turn it into machine code, that a computer can understand and execute [49]. The situational factors grouped under this category are source code attributes, source code change attributes, source code change documentation, testing, review concentration, and defect [17], [18], [19], [32], [43] [50], [51], [52], [53], [54], [55].…”
Section: ) Peoplementioning
confidence: 99%